Implementation of Project Based Learning Model to Increased Creativity and Self-Reliance of Students on Poetry Writing Skills (Universitas Negeri Semarang, 2019)
The purpose of this study was to determine the influence of Project Based Learning models to increase the creativity and self reliance of students on the skills of writing poetry. The research is a Pre-Experimental One Group (pretest-posttest) design. These samples included 48 students without cotrol class. Pretest is given at the beginning of the learning before the implementation of the Project Based Learning model and posttest in the end of the learning process. The results showed a significant increase in the implementation of Project Based Learning to creativity and self reliance on the skills of writing poetry. Based on N-Gain test shows the students’ creativity increase of 0.45 (medium). The values indicator of creativity divided ito three points are fleuncy, flexibelity, and originality. Students’ self reliance on the skills of writing poetry after implementation of Project Based Learning models contained in the high category. For the score of students on poutry writing skill is shows a good increased. The values indicator on poutry writing skill divided into five poits are preparation of stanza, rhyme, diction, the use of punctuation, and content. The response of learners very well to learning, for the further study with the model Project Based Learning can be recommended for implementation in schools.